KESANTUNAN LINGUISTIK: BAGAIMANA MENELITINYA DI MASYARAKAT PRAKTISI KITA (SEBUAH INSPIRASI DARI RICHARD J. WATTS) - Sri Minda Murni (BAHAS, 2010)
Indonesian politeness system is one of among the most complicated and systematic politeness system in the world. In fact, it is hardly to define what Indonesian politeness is and how it works due to the huge diversity featuired by the 583 ethnic languages and dialects existed in the country. Other important considerations are the large number of  communities of practice existed in the society. Two important sources of inspiration to the Indonesia politeness system are: Islamic religion and cultural values. Watts’s approach on research on linguistic politeness is relevant as to how to define the Indonesian politeness system by considering the differences between the politic and  polite behavior as well as the socially stricted and individually chosen strategies. Kata Kunci: politic behavior, polite behavior, socially-stricted utterances, strategically-chosen utterances, community of practice.